Factors Influencing Wound Healing Complications After Wide Excision of Injection Site Sarcomas of the Trunk of Cats. Issue 7 (26th May 2014) - Cantatore, Matteo; Ferrari, Roberta; Boracchi, Patrizia; Gobbetti, Matteo; Travetti, Olga; Ravasio, Giuliano; Giudice, Chiara; Di Giancamillo, Mauro; Grieco, Valeria; Stefanello, Damiano
<x xml:space="preserve">Abstract</x> Objective Wide surgery is the mainstay of the multimodal treatment of injection site sarcomas (ISS) in cats. The aim of the study was to analyze potential factors influencing the development of wound healing complications (WHC) in cats undergoing wide excision of ISS. Study design Retrospective case series. Animals Forty‐nine cats with ISS located on the trunk underwent wide excision after contrast‐enhanced computed tomography planning. Methods The prognostic effect of covariates (sex, age, weight, body condition score (BCS), site, clinical dimension (CD), computed tomographic dimension (CTD), histotype, duration of surgery, surgical margin status, local anesthesia) on total, major and minor WHC was evaluated by univariate and bivariate analysis. Cox model was used for total WHC and Fine and Gray model was used for major and minor WHC. The relationship between duration of surgery and clinical and imaging variables was evaluated. Results The main factor associated to the risk of total and major WHC was surgical time. Based on univariate analysis, pattern of reconstruction, CDT, CD, weight, and BCS were significant prognostic factors for major WHC, but this was not confirmed when adjusted for other clinical variables in bivariate analysis. The duration of surgery was influenced by excision pattern and tumor CTD width. Conclusions An increased duration of surgery as the consequence of complex surgical procedures represented the best predictor for the development of WHC.